2021
DOI: 10.37464/2020.383.147
|View full text |Cite
|
Sign up to set email alerts
|

Community-based nurse practitioner support is associated with better self-care behaviour and quality of life in patients with chronic heart failure

Abstract: Objective: To evaluate the effects of a communitybased chronic heart failure management program, delivered by nurse practitioners, on self-care behaviour, quality of life and hospital readmissions.Background: Chronic heart failure is a complex condition associated with high rates of hospital readmissions. However, many hospitalisations in patients with chronic heart failure are potentially preventable with better self-management and access to specialised healthcare support. Nurse practitioners have an advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…31 Accordingly, they are well credentialed to apply case management for patients with HF. We have recently reported that an NP-led HF clinic can improve self-care behaviour and quality of life, and reduce hospital admissions, 32 highlighting the efficacy of HF models of care involving NPs.…”
Section: Introductionmentioning
confidence: 99%
“…31 Accordingly, they are well credentialed to apply case management for patients with HF. We have recently reported that an NP-led HF clinic can improve self-care behaviour and quality of life, and reduce hospital admissions, 32 highlighting the efficacy of HF models of care involving NPs.…”
Section: Introductionmentioning
confidence: 99%